THE EFFECTIVENESS OF USING VISUAL VOCABULARY APPLICATION TO IMPROVE STUDENT’S VOCABULARY MASTERY - Kartiasih, Titin; Usman, Sriati; Dewi, Anjar Kusuma; Mukrim, Mukrim (e-Journal of ELTS (English Language Teaching Society), 2023)
The objective of the research is to find out whether or not the media can improve vocabulary mastery of the seventh grade students of SMP Negeri 32 Sigi. The researchers focused on noun and adjective. In this research, the researchers used a quasi-experimental design. The researchers used Visual Vocabulary Application as a media. The experimental group consisted 22 students, while the control group consisted 25 students. The instrument in collecting the research data was a test. The test was given to students twice as pre-test and post-test. The data were analyzed statistically. Students’ mean score of experimental group of pre-test (30.45) and post-test (65.22) is 36.59. While the control group of pre-test (20.6) and post-test (35) is 16.2. It means that Visual Vocabulary Application is significantly improve the ability of the seventh grade students of SMP Negeri 32 Sigi.